Qualitative, Quantitative, GCMS, and FTIR Phytochemical Screening of Cassia occidentalis - Ahmad, K. A. (Darul Yasin Al Sys, 2025)
Cassia occidentalis Linn, a plant widely recognized in traditional medicine, was subjected to comprehensive phytochemical analysis to elucidate its bioactive constituents. Both qualitative and quantitative assessments confirmed the presence of key secondary metabolites, including alkaloids, flavonoids, phenolic acids, saponins, steroids, and terpenoids. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of the methanolic extract identified 30 distinct compounds, notably hexadecanoic acid methyl ester, cis-9-hexadecenal, oleic acid, 9-octadecenoic acid methyl ester, and 9,17-octadecadienal, all of which are associated with antimicrobial, antioxidant, and anti-inflammatory properties. Fourier Transform Infrared Spectroscopy (FTIR) further confirmed the presence of characteristic functional groups such as hydroxyl, carboxyl, and alkene groups, supporting the structural integrity of the compounds identified via GC-MS. These findings provide a detailed phytochemical profile of Cassia occidentalis, offering a scientific foundation for its traditional therapeutic applications and supporting its potential for further pharmacological investigation.